Established tools and emerging trends for the production of recombinant proteins and metabolites in Pichia pastoris. Issue 2 (26th July 2021) - De, Sonakshi; Mattanovich, Diethard; Ferrer, Pau; Gasser, Brigitte
Abstract: Besides bakers' yeast, the methylotrophic yeast Komagataella phaffii (also known as Pichia pastoris ) has been developed into the most popular yeast cell factory for the production of heterologous proteins. Strong promoters, stable genetic constructs and a growing collection of freely available strains, tools and protocols have boosted this development equally as thorough genetic and cell biological characterization. This review provides an overview of state-of-the-art tools and techniques for working with P. pastoris, as well as guidelines for the production of recombinant proteins with a focus on small-scale production for biochemical studies and protein characterization. The growing applications of P. pastoris for in vivo biotransformation and metabolic pathway engineering for the production of bulk and specialty chemicals are highlighted as well.